Clinical Variability and Genotype‐Driven Outcomes in CHRND ‐Related Congenital Myasthenic Syndrome - David Muhmann; Göknur Haliloğlu; Maria Antonia Grimalt; Damjan Osredkar; Ana Vesperinas Castro; Silvia Cerezo Corredera; Angela Abicht; Adalet Elçin Yıldız; Johann Böhm; Ulrike Schara‐Schmidt; Anja Troha Gergeli; Berta Estevez‐Arias; et al. (European Journal of Neurology, 2026)
ABSTRACT Background Congenital myasthenic syndromes (CMS) caused by pathogenic variants in CHRND , encoding the δ‐subunit of the nicotinic acetylcholine receptor (AChR), are rare, and data on genotype–phenotype correlations and long‐term outcomes are limited. Methods We performed a retrospective, multicenter study of nine patients with genetically confirmed CHRND ‐related CMS from specialized neuromuscular centers. Clinical, electrophysiological, genetic, and therapeutic data were systematically collected. All diagnoses were established by exome sequencing during routine clinical work‐up. Results Eight patients were compound heterozygous and one was homozygous for pathogenic CHRND variants, including nonsense, missense, splice‐site variants, and one microdeletion. Disease onset ranged from the neonatal period ( n = 7) to adolescence ( n = 2). Three patients were followed longitudinally for 22–43 years. Ocular involvement, particularly ptosis and ophthalmoparesis, was present in all patients. Generalized fatigable weakness was common, whereas bulbar and respiratory involvement occurred in a subset and reflected overall disease severity. Genotypes including a null allele or a homozygous missense variant tended to be associated with more severe phenotypes, while compound heterozygous missense variants were linked to a broader and generally milder spectrum, sometimes limited to ocular symptoms. Long‐term outcomes ranged from minimal symptoms under therapy to severe motor impairment with respiratory insufficiency, highlighting substantial interindividual variability. Conclusions This study expands the phenotypic and genotypic spectrum of CHRND ‐related CMS and underscores the critical role of genotype in determining disease severity. Comprehensive genetic testing, longitudinal phenotyping, and genotype‐informed management are essential for optimal diagnosis and care in this rare disorder.